Nurses’ views on self-control of emotions in caring for dying patients-preliminary study - Anna Fąfara; Anna Barbara Krakowiak-Burdzy; Magda Penar (Medical Research Journal)
INTRODUCTION: One of the most important people in the last days of a patient’s life is the nurse. The nurse, performing basic care and nursing activities, becomes one of the closest people to the patient. The nurse is often accompanied by certain emotions with which she must deal. Notoriously working with one’s own emotions is a huge emotional effort, and the lack of reformatting negative experiences can eventually lead to symptoms of psycho-physical fatigue and professional burnout. AIM: The study aimed to find out nurses’ opinions on self-control of emotions in caring for a dying patient. MATERIAL AND METHODS: The present study used a diagnostic survey method, based on the survey technique. The research tools used were the author’s survey questionnaire and the Courtauld Emotional Control Scale (CECS). The study group consisted of 110 nurses working in terminal facilities in the city of Rzeszow between February and May 2023 in direct contact. Participation in the study was voluntary, random, and anonymous. RESULTS: Feeling sadness did not affect the level of difficulty in caring for a dying patient, while the occurrence of fear of the death of a loved one did. Nurses who experience this feeling during the death of a patient have more difficulty in comprehensive patient care, as well as in communicating with the patient’s family. Individuals in whom the death of a patient may change the hierarchy of values are characterized by a lower ability to suppress depression. CONCLUSION: The occurrence of incidents of anxiety and anger among nurses affects poorer performance of selected tasks and duties in caring for a dying patient. Nurses who react badly psychologically and experience stress at the death of a patient have higher difficulties in the comprehensive care of such a patient.